The discovery and importance of the higgs boson - Pereira da Silva, Jizreel (International Journal of Physical Research, 2022)
This work presents the importance of the existence of the Higgs boson, a particle with a mechanism capable of generating mass for other elementary particles, where interacting particles receive mass and those that do not interact, do not receive mass. The work shows the understanding of the mechanism for the interactions of particles with the Higgs boson and analysis of the experiments carried out at CERN, together with other detectors such as CMS and ATLAS, in the search over 50 years for the physicist Peter Higgs, suggesting a new theory necessary for the existence of the mechanism that would generate mass for the other particles. Even with the scientific advance through the discovery of the Higgs boson and its explanation within the Standard Model, we still have questions to be answered by not explaining gravitational interaction, hierarchy problem, extra dimensions, supersymmetry, dark matter, among others. The discovery and importance of the Higgs boson is another achievement for science, int the sense that we are on the right path, even recognizing the limitations of equipment and investments, but in the search for the truth and answer in favor of a more structured society, such as improved health, living in an environment with less pollution, advancement in technology, resulting in several positive factors for humanity.Â Â